Krisis Femisida di Meksiko sebagai Kegagalan Negara dalam Perlindungan Gender - Putri Rizka Nurwijedah Kadir (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
Gender-based violence has become a growing global problem, but in Mexico, the phenomenon of femicide has reached a concerning crisis level. Femicide, or the killing of women because of their gender identity, reflects the most extreme form of inequality and injustice experienced by women in society. This study seeks to examine the femicide crisis in Mexico as a manifestation of the state's failure to fulfill its obligation to protect women's rights. Through a qualitative descriptive approach, this study analyzes how weak legal institutions, high rates of impunity, and a deeply rooted patriarchal culture exacerbate the situation of violence against women. In addition, this study also examines the extent to which Mexico has implemented international standards, especially the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW), and how the state has failed to implement them effectively. Using the concept of state failure, this study concludes that the femicide crisis in Mexico is not only a social problem, but also reflects the state's structural inability to provide equal legal protection and justice for women. Therefore, there needs to be a comprehensive reform of the legal system and gender-responsive public policies based on human rights principles. Therefore, increasing institutional capacity and strengthening public accountability mechanisms are important steps so that the state is no longer negligent in handling femicide and is truly present for victims in a real and comprehensive manner.